Movies are prayers : how films voice our deepest longings - Larsen, Josh, 1974- (InterVarsity Press, 2017)
Movies do more than tell a good story. Filmspotting co-host Josh Larsen brings a critic's unique perspective to how movies can act as prayers--expressing lament, praise, joy, confession, and more. When words fail, the perfect film might be just what you need to jump-start your conversations with the Almighty.